PENGAWASAN KEKUASAAN KEHAKIMAN DALAM NEGARA HUKUM INDONESIA - Satriya Nugraha (Fakultas Hukum Universitas PGRI Palangkaraya, 2017)
Abstract : Research on the supervision of judicial power in Indonesian legal state, is based on the normative research method. The problem is about the external control of the legislative power over the judicial authorities in Indonesia. From this research, it has been found that within the perspective of the state law, Judicial Power or Judicial Power (Yudiciare) has authoritative powers in overseeing the implementation of the Act implemented by the Executive. General oversight both in the strict sense and loosely equally have internal controls on judicial performance and functionally oversees the Judiciary institutions. External Oversight of Judicial Power exercised by the executive is relatively small, precisely the performance of the judicial power of the past a lot of supervision in the form of interpretation and even changes to the legislation Legislative Product. This happens as an implementation of the theory of separation of power which is constitutionally regulated. Internal control within which there is an ethical dimension is the supervision of the freedom of Judicial Power based on moral rules (ethics) which must be ignored by the exercise of Judicial Power (Judge) in performing Judicial functions even though it is outside the Law but there is a connection with the normative and institutional external limits. Keywords : Community Monitoring, Judicial Commission, Court Performance.